Determining factors of the business growth in MSMEs affected by COVID-19 - Murrell-Blanco, Manfred (2022)
The health crisis caused the SARS-CoV-2 and his disease the COVID-19 has significantly affected companies both nationally and internationally, triggering a series of negative consequences on critical success factors such as sales and hire.  The purpose of this research was to analyze the incidence of variables such as the employer gender, age and size of the company, and the support of suppliers in the economic activity of Costa Rican MSMEs in the context of the health and economic crisis. To prepare this study, a database collected by the Ministry of the Economics of Industry and Commerce (MEIC) was used, corresponding to a sample of 2718 MSMEs from the business park. A Logistic Regression Model was used for data analysis, which allowed us to examine the significant statistical relationships of the variables studied. The results support a significant relationship between the company’s size concerning the level of sales and the hiring of personnel. On the other hand, they point out that there is no significant relationship between the gender of the owners or administrators and the age of the MSMEs to the two dependent variables.